Tinjauan terhadap Proses Pengawasan oleh Balai Pemasyarakatan terhadap Narapidana Penerima Pembebasan Bersyarat: Studi pada Balai Pemasyarakatan Kelas I Bandar Lampung - Diva Okta Nurkhalifa; Diah Gustiniati; Fristia Berdian Tamza; Dona Raisa Monica (Majelis: Jurnal Hukum Indonesia, 2025)
Parole is an important instrument in the social reintegration of inmates, with the Correctional Center (Bapas) playing a role in guidance, assistance, and supervision. This study analyzes the implementation of supervision by the Class I Correctional Center in Bandar Lampung for parole clients, as well as the obstacles encountered. The research employs a normative juridical and empirical approach, using both primary and secondary data, with sources including the Head of the Adult Client Guidance Section and a Criminal Law Lecturer at the University of Lampung. The findings indicate that supervision has been optimal, with no cases of parole revocation. The main obstacles include the absence of clear administrative sanctions, limited authority, weak law enforcement, inadequate facilities and technology, lack of inter-agency coordination, low public participation, and unsupportive client behavior. Improvements in regulations, enhancement of human resources quality, provision of adequate facilities, and strengthening community involvement are required to support the success of social reintegration